Risk simulation of having direct contact with electric urban networks - Fernando Martínez Santa; Fredy H. Martínez; Edwar Jacinto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
To know the electric risks for the human health having electric discharges on low and medium voltage urban networks, helps to the people to make aware about doing actions of prevention and safety, which reach to prevent injuries and/or accidental deaths. In this paper, simulations on ATP-Draw software over three different specific risk cases were done, based on the concurrent problem presented in the central region of Colombia between august and october when people use to fly kites. The first case analyzed is an individual who has an indirect contact with medium voltage transmission lines by means on a conventional kite, presenting no serious effects on its health. In the second and in the third case, the individual generates a direct contact both low and medium voltage lines, when tries to recover a stuck kite, receiving high health effects even producing death. The main goal of this work is to show the different consequences and effects in the human body which are presented over a person when receiving an electric discharge by direct contact, in order to prevent accidents.